A new computer-assisted method for measuring the tibio-femoral angle in patients with osteoarthritis of the knee - Takahashi, T.; Yamanaka, N.; Komatsu, M.; Ogawa, Y.; Yoshida, S.; Yamamoto, H. (Osteoarthritis and cartilage, 2004)
Objective: The purpose of this study was to evaluate the inter- and intraobserver variability in measuring the tibio-femoral angle using our new computer-assisted method, and to compare it with a conventional manual method. Methods: Radiography of all patients of osteoarthritis of the knee in outpatient were performed with standing on both legs, and with conventional antero-posterior weight bearing view of the knee fully extended. Three examiners measured the tibio-femoral angle with the computerized method in 52 subjects with osteoarthritis (73 knees). The tibio-femoral angle was measured using a computer-assisted method in which the observer must visually determine and select eight points on the margins of the femur and tibia on a radiographic image displayed on a computer monitor. The inter- and intraobserver Intra-class correlation (ICC) was analyzed. Results: The interobserver mean correlation of computer-assisted method was 0.970 with a mean difference of 0.38° ( s.d. 1.125°). The intraobserver mean ICC of computer-assisted method was 0.973, with a mean difference of 0.16° ( s.d. 1.12°). An analysis of the difference between conventional methods and our new system showed a mean ICC of 0.922, with an intersystem mean difference of 0.295° ( s.d. 1.82°). Conclusion: Our computer-assisted method of measuring the tibio-femoral angle was simple, easy, and quick, and should be considered as an alternate method for measurement.